NEED-DRIVEN MANPOWER DEVELOPMENT FOR THE METALLURGICAL AND MATERIALS INDUSTRY BY ENGINEERING CURRICULUM RESTRUCTURING (2009)
Development and enhancement of innovative engineering curriculum is a vital exercise in producing well grounded graduates that can perform in today's world. In this paper, two existing models on developing metallurgical engineering curriculum were outlined: The Russian model where there is early specialization to meet national interest and the western model where there is emphasis on acquiring basic engineering principles with some form of introduction to specializations in the senior year. The merit and/or demerits of the two models were discussed. In developing undergraduate metallurgical engineering cuuriculum, it was adjusted best to strike a balance between the future of the student (academics and job), the needs of the employer and the nation for reasons of academic progression, job safety and global relevance.